Hypertriglyceridemia in patients with metastatic breast cancer and treatment with capecitabine. (1st June 2013) - Geva, Shahar; Lazarev, Irena; Geffen, David Barry; Ariad, Samuel
Abstract : Several reports have described hypertriglyceridemia (HTG) in cancer patients, including breast cancer patients treated with capecitabine (CAP). However, the exact range of HTG in patients with metastatic breast cancer (MBC) treated with CAP has clearly not been defined. A retrospective analysis on 54 patients with MBC treated with CAP longer than 2 months was conducted. HTG was defined as triglyceride blood level above 150 mg/dl. Baseline data included age, body mass index (BMI), tumour characteristics, treatment duration, concomitant treatment with lapatinib, diagnosis of dyslipidemia, and diabetes mellitus, as well as antihyperlipidemic therapy. Clinically significant HTG (triglycerides >300 mg/dl) was found in 4/54 (7%) of patients. Post-treatment HTG was associated only with concomitant treatment with lapatinib ( P <0·01). Three of the patients had dyslipidemia before treatment with CAP, and one patient also had diabetes-mellitus. No HTG-related complications occurred. Clinically significant HTG in MBC patients treated with CAP may be associated with pre-existing risk factors, such as dyslipidemia or diabetes-mellitus.